Antireflux mucosectomy for gastroesophageal reflux disease: efficacy and the mechanism of action - Kuipers, Thijs; Oude Nijhuis, Renske A.B.; Pouw, Roos E.; Bredenoord, Albert J. (Endoscopy, 2024)
Background Previous studies suggested that antireflux mucosectomy (ARMS) is effective in reducing reflux symptoms and total acid exposure, although the mechanism is unknown. Our objective was to investigate the effect of ARMS on reflux parameters and its mechanism of action.Methods Gastroesophageal reflux disease (GERD) patients with insufficient symptom control despite a twice-daily proton pump inhibitor (PPI) underwent a piecemeal multiband mucosectomy of 50% of the circumference of the esophagogastric junction (EGJ), extending 2 cm into the cardia. The primary end point was the total number of reflux episodes during 24-hour pH-impedance studies.Results 11 patients (8 men; median age 37 [interquartile range (IQR) 32–57] years) were treated, with one patient subsequently lost to follow-up. ARMS reduced the median (IQR) number of total reflux episodes (74 [60–82] vs. 37 [28–66]; P = 0.008) and total acid exposure time (8.7% [6.4%–12.7%] vs. 5.3% [3.5%–6.7%]; P = 0.03). Treatment reduced the median (IQR) number of transient lower esophageal sphincter relaxations (TLESRs) during a 90-minute postprandial period (4 [1–8] vs. 2 [1–4]; P = 0.03) and reflux symptom scores (3.6 [3.6–3.9] vs. 1.6 [0.7–2.7]; P = 0.005). Treatment did not increase the mean (SD) dysphagia scores (8.2 [7.3] vs. 8.5 [6.5]) or change the EGJ distensibility on impedance planimetry (4.4 [2.1] vs. 4.3 [2.2] mm2/mmHg). One delayed post-procedural bleed requiring repeat endoscopy occurred (10%); no strictures developed.Conclusion ARMS is an effective treatment option in PPI-refractory GERD, reducing acid exposure, reflux episodes, and symptoms. While its working mechanism could not be explained by a difference in distensibility, a reduction in TLESRs might play a role.